2015
DOI: 10.1063/1.4916339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrostatic pressure on magnetostructural transitions and magnetocaloric properties in (MnNiSi)1−x(FeCoGe)x

Abstract: Magnetostructural transition and magnetocaloric effect in MnNiGe1.05 melt-spun ribbons J. Appl. Phys. 115, 17A920 (2014); 10.1063/1.4864435 Effect of substitution of In for Co on magnetostructural coupling and magnetocaloric effect in MnCo1-xInxGe compoundsThe isostructural alloying of two compounds with different magnetic and thermo-structural properties has resulted in a new system, (MnNiSi) 1Àx (FeCoGe) x , that exhibits large magnetocaloric effects with acute sensitivity to both compositional variation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Among the hundreds reported compounds that exhibit the "giant" magnetocaloric effect [29] have been identified as the most promising, and the phenomenon itself has been confirmed in a number of intermetallics [13,[29][30][31][32][33][34][35][36][37]. Many of the known materials exhibiting the strongest giant magnetocaloric effect, however, contain elements that are precious (e.g., Rh), expensive (e.g., Ge, In), toxic (e.g., As or P), or non-earth-abundant (e.g., Gd and Y), and they often require complex and lengthy synthesis and processing sequences to make them useful.…”
Section: The Materials Challengementioning
confidence: 99%
“…Among the hundreds reported compounds that exhibit the "giant" magnetocaloric effect [29] have been identified as the most promising, and the phenomenon itself has been confirmed in a number of intermetallics [13,[29][30][31][32][33][34][35][36][37]. Many of the known materials exhibiting the strongest giant magnetocaloric effect, however, contain elements that are precious (e.g., Rh), expensive (e.g., Ge, In), toxic (e.g., As or P), or non-earth-abundant (e.g., Gd and Y), and they often require complex and lengthy synthesis and processing sequences to make them useful.…”
Section: The Materials Challengementioning
confidence: 99%
“…The discovery of the giant MCE in Gd 5 Si 2 Ge 2 [10] prompted worldwide research to exploit first-order magneto-structural transitions (MSTs) to achieve large MCEs. As a result, a number of materials exhibiting giant magnetocaloric effects, such as those based on La-Fe-Si [11], Fe 2 P [12], MnTX (T = transition metal, X = p-block element) [13,14], MnAs [15,16], and some Heusler alloys [17], were discovered and characterized. These state-ofthe-art materials are, unfortunately, far from ideal: some contain hazardous, critical or non-earth-abundant elements, while others involve complex syntheses and processing.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 21,22 have realized the coupling of magnetic and structural transitions in MnNiSi system by doping with Fe, Ge or Al atoms. 21,22 Samanta et al 10,23 have alloyed MnFeGe and FeCoGe with MnNiSi, respectively, and studied the effects of hydrostatic pressure on the magnetostructural transition and magnetocaloric properties. 10,23 Li et al 24 have reported the substitutional effects of Fe and Co at the Mn-sites, which shows a significant decrease of T t .…”
Section: Introductionmentioning
confidence: 99%